Evaluation of spatial interpolation methods and spatiotemporal modeling of rainfall distribution in Peninsular Malaysia - Fung K.F.; Chew K.S.; Huang Y.F.; Ahmed A.N.; Teo F.Y.; Ng J.L.; Elshafie A. (Ain Shams University, 2023)
Atmospheric thermodynamics; Interpolation; Inverse problems; Rain; Scales (weighing instruments); Geographical weighted regressions; Interpolation method; Inverse distance weighting; Rainfall distribution; Spatial interpolation; Spatial interpolation method; Spatio-temporal models; Spatiotemporal analysis; Climate change